Design and Performances of Multi-Tooth Stator Permanent Magnet Flux Switching Machine for Light Weight Applications - Omar, M. F.; Sulaiman, E.; Jusoh, L. I.; Othman, S. M. N. S.; Badrudden, S. A. L. S. (International Journal of Engineering and Technology, 2018)
Permanent magnet flux switching machines (PMFSMs) in which their torque performance produced by interaction between armature coils and permanent magnet (PM) have been widely designed for various applications. In this regard, single-phase 8Slots-12Poles PMFSM with single tooth stator is considered the most suitable candidate for light weight applications because of their advantages of lower copper loss, high efficiency and robust rotor. However, issues of low torque performance due to weak flux linkage, high of PM volume, and high distortion in back-emf that need to be improved. In this paper, a new design of single-phase PMFSM using multi-tooth stator is proposed. Both PMFSMs have been designed using JMAG Designer version 15 and analysed through 2D-FEA. Parameters of stator outer radius, rotor outer radius, air gap, and stack length are set to 37.5mm, 22mm, 0.25mm, and 20.3mm, respectively. Based on the 2D-FEA, PM flux linkage and torque performances of the PMFSM using multi-tooth are 5 times and 38% higher than PMFSM using single-tooth. As a conclusion, single-phase 4Slot-12Poles PMFSM using multi-tooth stator considered as the best candidate for light weight applications due to the less PM volume, and good performances of toque, power and based speed of 1.44Nm, 219W, 1,062rpm, respectively.